Electromagnetic wave absorption properties of FeCoNiCrAl0.8 high entropy alloy powders and its amorphous structure prepared by high-energy ball milling. Issue 16 (29th July 2016) - Yang, Peipei; Liu, Ying; Zhao, Xiuchen; Cheng, Jingwei; Li, Hong
Abstract: Abstract : We investigated FeCoNiCrAl0.8 high entropy alloy and amorphous alloy powders synthesized simply via high energy ball milling for 10 and 20 h. The electromagnetic wave absorption properties of FeCoNiCrAl0.8 high entropy alloy and amorphous alloy powders were investigated. The structure and morphology of FeCoNiCrAl0.8 were analyzed by scanning electron microscopy with energy-dispersive spectrometry and x-ray diffraction, which demonstrated that FeCoNiCrAl0.8 powders were in irregular shape and monodisperse with an average size of 5–15 µm. The minimum reflection loss of FeCoNiCrAl0.8 high entropy alloy powders was −41.8 dB at 11.9 GHz with a thickness of 2.3 mm and effective bandwidth (RL ≤ −10 dB) was up to 4.7 GHz (8.7–13.4 GHz), while the minimum reflection loss of FeCoNiCrAl0.8 amorphous alloy powders was observed to be −35.5 dB at 14.6 GHz with a thickness of 1.7 mm and effective bandwidth varied from 12.7 to 16.3 GHz (3.6 GHz). Electromagnetic wave absorption properties of FeCoNiCrAl0.8 high entropy alloy powders is better than that of amorphous alloy powders, which demonstrated that phase structures of FeCoNiCrAl0.8 alloy powders affect electromagnetic wave absorption properties.